A Cognitive Linguistic Study of Battered Woman in Selected Iraqi Caricatures (Journal of the College of Education for Women, 2022)
The present paper is a qualitative descriptive study. It aims to examine the macro-cultural schemata addressing the concept of violence against women in Iraq from a cognitive linguistic point of view. To meet this objective, a number of Iraqi social caricatures have been selected from two popular and active Iraqi caricaturists, Odeh Al-Fahdawi and Nasser Ibrahim. The selection and the analysis of data have been achieved following the validity and reliability procedures and the ethical considerations. To meet this objective, Sharifian’s Model (2011) of Cultural Schemata has been adopted in data analysis. The study has concluded that the macro-cultural schemata regarding the concept of violence in the selected panels reveals that violence against women does exist in the Iraqi society, and that woman and children are the major victims of that phenomenon. Moreover, the major cause of such a phenomenon is due to the patriarchal nature of the society that leads to have an unbalanced power between the two parties man vs. woman/children; in addition to other reasons related to the unfair social traditions and customs. The mismatch in power has been conceptualized creatively and differently by these two caricaturists. Speaking from the cognitive linguistic point of view, the researchers have also found that the panels are symbolic rather than iconic, as they involve culture-proper figures. Finally, both caricaturists invested the conceptual metaphors and figurative devices when depicting the concept of violence against women; that is, the concept of violence against women is universal in their panels; however, the way it is depicted is subjective and cultural-proper at the micro-cultural level.